Legal issues in nursing documentation - Jahn Kassim, Puteri Nemie (2012)
Nursing documentation is an integral part of nursing and midwifery practice. It is a tool of professional practice that helps in the care process. When matters are brought to court, this document furnishes documentary evidence of the course of care to the patient. This document is therefore, crucial in defending allegations of medical malpractice and thus, protecting the nurses’ as well as the hospital’s legal interest.